THE AGROTECHNICS OF THIN-FIBER COTTON VARIETIES UNDER CONDITIONS OF STRESS FACTORS (Conferencea, 2023)
Stress factors have a serious negative impact on living organisms, including plants. As a result, the productivity indicators of plants and the harvest and its quality are decreasing. Intensification of scientific research aimed at reducing the negative effects of such stress factors and development of measures to save the lost crop, assessment and justification of the physiological aspects of the effects of adverse stress factors are considered as the most important tasks [1-4].